What triggers sharing in viral marketing? The role of emotion and social feature - Li, Boying; Chong, Alain Yee-Loong; Ch’ng, Eugene (2015)
Viral marketing has attracted attention from both academics and practitioners. With the rise of user-generated content (UGC) and broadcasting networks, viral online video advertising campaigns (viral advertising in short) are an emerging trend in viral marketing. Previous literature mainly studied the influence of network structure on viral advertising. Here, we extend such works by decomposing the diffusion network into individual sharing behavior. We based our work on theories of emotion and social networks by proposing a framework that specifies the role of emotion and social feature on individuals’ sharing of online video advertisements in viral marketing campaigns. The framework will be tested using real-world data extracted from online broadcasting networks in the future work.